Z badań nad językiem młodego pokolenia na ziemiach zachodnich = Researches on the Linguistic Habits of the Young Generation in the Western Parts of the Country - Bułczyńska-Zgółka, Halina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This work intends to show same aspects of linguistic integration occuring in the Western Parts of this country. Schoolworks of pupils from Elementary Schools in Babimost and Podmokle in the district of Zielona Góra are the basic material for deliberations of dialectological and even sociolinguistical significance. In the above mentioned places one can observe the formation of a new and mixed dialect characteristic for those Western Parts of the country.The researches embrace also the regional descent of the pupil`s parents, what is of the utmost importance in the interpretation of dialectic occurences.
Keywords: język polski; badania; młodzież; Ziemie Zachodnie